Peran Corporate Governance dan CSR dalam Mengendalikan Agresivitas Pajak Dimoderasi Financial Distress - Andri Satria; Ninuk Dewi Kesumaningrum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to obtain empirical evidence regarding the effect of corporate governance and corporate social responsibility disclosure on tax aggressiveness with financial distress as a moderating variable. The population in this study was manufacturing companies listed on the Indonesia Stock Exchange during the period 2019-2023. The sample was selected using a purposive sampling technique, resulting in 70 companies with 350 analysis units (panel data). The results of this study indicate that corporate governance proxied by independent commissioners has a significant negative effect on tax aggressiveness. Meanwhile, corporate governance proxied by institutional ownership, managerial ownership, and audit committees has no effect on tax aggressiveness. In addition, CSR disclosure also has no effect on tax aggressiveness. Financial distress is proven weaken the negative relationship between independent commissioners and tax aggressiveness, but is not proven to weaken the negative relationship between institutional ownership, managerial ownership, audit commitees, and CSR disclosure on tax aggressiveness. This study is provides for stakeholders, such as managers, shareholders, and the government in developing strategies to reduce tax aggressiveness practices.